2022
DOI: 10.7150/ijbs.69802
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-CoA synthetase long-chain 3-mediated fatty acid oxidation is required for TGFβ1-induced epithelial-mesenchymal transition and metastasis of colorectal carcinoma

Abstract: Cancer cells frequently undergo metabolic reprogramming to support tumorigenicity and malignancy, which is recognized as a hallmark of cancer. In addition to glycolysis and glutaminolysis, alterations in fatty acid (FA) metabolism have received increasing concerns in the past few years. Recently, accumulating evidence has shown that fatty acid β-oxidation (FAO) is abnormally activated in various tumors, which is associated with the machinery of proliferation, stemness, metastasis, and radiochemotherapeutic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Therefore, we presumed that the miR-33a-5p/ CROT axis plays an important role in mediating OC cell behaviors. Furthermore, the positive regulation of TGF-b on fatty acid oxidation has been observed in breast and colorectal cancer cells (42,43), implying that TGF-b may also be involved in CROT-mediated OC cell behaviors. Indeed, GSEA enrichment analysis showed the negative relationship between CROT and TGF-b signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we presumed that the miR-33a-5p/ CROT axis plays an important role in mediating OC cell behaviors. Furthermore, the positive regulation of TGF-b on fatty acid oxidation has been observed in breast and colorectal cancer cells (42,43), implying that TGF-b may also be involved in CROT-mediated OC cell behaviors. Indeed, GSEA enrichment analysis showed the negative relationship between CROT and TGF-b signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Little is known about the regulatory role of lipogenesis genes in EMT. Transforming growth factor beta 1 (TGFβ1) has been reported to induce the up‐regulation of acyl‐CoA synthetase long‐chain 3 (ACSL3) expression promoting metabolic reprogramming in colorectal carcinoma (CRC) cells, ACSL3 also mediates EMT and metastasis of CRC cells by activating the fatty acid β‐oxidation (FAO) pathway, which stimulates ATP production and inhibits the level of nicotinamide adenine dinucleotide phosphate (NADPH) [ 69 ]. Previous study has shown that TGFβ and leptin can inhibit the activity of ACC1 through AMPK‐catalyzed phosphorylation of ACC1 at Ser79, thereby promoting EMT, ACC1 inhibition combined with concomitantly increased acetylation of SMAD2, which is triggered by accumulated acetyl‐CoA, mediates TGFβ‐induced EMT [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deregulation of choline metabolism is intensively involved in the pathogenesis and development of cancers, and thus is considered to be one of the metabolic hallmarks of cancer [ 31 34 ]. Deregulation of choline metabolism contributes to tumorigenesis, progression, invasiveness, and therapeutic resistance [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%